ACCOMPANIENT IN SERVICE MARK REGISTRATION AS LEGAL AID TO SURYA JAYA MOTOR WORKSHOP - Tantimin Tantimin; Suryasan Lau (Universitas Internasional Batam, 2022)
In the industrial era 4.0, it is a situation where all technology is very sophisticated, and will still develop every time. Advances in technology are not only a matter of transportation but have an impact on all sectors of human life. Especially for business, business competition is increasing so that many businesses have sprung up. Having a business without a physical store is not impossible. Businesses can be started through their own homes using an online platform, all people can sell. Not only quality as an attraction to consumers or buyers, but service is also important considering the increasingly fierce business competition. Therefore, an identity for business ownership is needed, namely in the form of a brand.